PERSEPSI ACCOUNT REPRESENTATIVE, KONSULTAN PAJAK DAN WAJIB PAJAK TERHADAP FAKTOR PENYEBAB TERJADINYA SHORTFALL DALAM PENERIMAAN PAJAK - Fisabela Apriliasari Rahmania (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The research aims to observe factors contributing to tax revenue shortfall as well as tax authorities efforts to overcome such problem. The research is a descriptive-qualitative study. The data are obtained from relevant literature and interview with respondents who directly involve in the tax system and considered as credible tax officers, tax consultants, and tax payers. The result shows that the main cause of tax revenue shortfall is because the targeted tax revenue of the state budget is too high. Self-assessment system is not supported by the socialization and the number of account representatives as taxpayer controllers is still inadequate which leads to non-compliance of taxpayers. Although tax compliance has improved compared to previous years, the results are still not maximized thereby reducing the amount of tax revenue. Preventive measures needed to be done by the government include the making of policy that facilitates taxpayers in order to ease the tax liabilities as well as releasing the tax amnesty’s police as soon as possible, increasing the number of human resources in the Directorate General of Taxation, and providing education and socialization of tax regulations on a regular basis to the entire community.Keywords: shortfall, tax revenue, tax officers, tax consultants, taxpayers, qualitative, descriptive, self-assessment.